Mean Amplitudes of Vibration of BrO ₂F⁻₂ and IO₂F⁻₂ - Baran, Enrique José (2001)
Mean amplitudes of vibration of the anions BrO ₂F⁻₂ and IO₂F⁻₂ have been calculated from vibrational spectroscopic data in the temperature range between 0 and 1000 K. Bond properties of these species are discussed on the basis of the obtained results and by comparison with known data for related molecules and ions.